Invisibility As A Metaphor: A Category Of Analysis To Identify The Invisibility Process In Social Problems. - Hernández López, Irma (2020)
The term invisibility has been widely used, in the social sciences, as a metaphor to give voice to vulnerable groups. In this work, a hermeneutic exercise is undertaken based on text that refer to this term. The impact of this metaphor, in social science research, is revealed. As a result, it was possible to reconstruct how the invisibility process develops, as well as, the circumstances under which it is decided to make the invisible visible. In addition, the agents, motivations, and reasons for the concealment are identified. The identified process follows a common pattern in the analyzed texts. It is concluded that the process of invisibility is dialectical, and there is a pattern to enhance invisibility and one to make the invisible visible. The results of this article are expected to be a catalyst to reflect on the potential of the invisibility metaphor to be considered as a category of analysis to understand, explain and address social problems. Keywords: metaphor; invisibility; visibility; hermeneutics; social sciences.